The Neuromyth of learning styles: The perception of Biological Sciences pre-service teachers at the University of Brasília, Brazil - Nóbrega, Maria Vitória Vieira da (2024)
In recent years, neuroscience has gained prominence in the field of education. However, those who seek to learn about neuroscience on their own may encounter inaccurate information or misconceptions about neuroscientific findings, known as neuromyths. One of the most widespread myths among educators is the one about Learning Styles (LS), which suggests that students learn best when information is presented according to their preferred style. This study aimed to investigate the perception of Biological Sciences students at the University of Brasília (UnB) regarding this neuromyth. To achieve this, an online questionnaire was administered to the participants. The results indicated that students have a positive view of Learning Styles. Therefore, it is necessary to debunk this neuromyth in the academic environment by integrating the study of neuroscience and educational neuromyths into initial teacher education through courses, research projects, and extension activities.